CONTEXTUALIZED ASTRONOMY TEACHING: : PRODUCTION OF A SOLAR SYSTEM DIDACTIC MODEL IN YOUTH AND ADULT EDUCATION (Interdisciplinary Studies Journal, 2026)
This study presents an intervention carried out with a third-year class of Youth and Adult Education (YAE) in a rural school, based on the construction of a Solar System model as a strategy for the integrated teaching of Science and Physics. The objective of the study was to report and reflect on the implementation of a didactic sequence, highlighting its contributions to meaningful learning, student engagement, and the understanding of scientific concepts. The practice was based on a qualitative approach, valuing students’ prior knowledge, life experiences, and dialogue as central elements of the educational process. The construction of the model enabled concrete visualization of planetary organization, general characteristics, and rotational and translational movements, reducing abstraction difficulties commonly associated with Astronomy teaching. The results indicated improvements in conceptual understanding, expansion of scientific literacy, and enhanced ability to interpret natural phenomena. Increased student participation, collaborative work, and protagonism were also observed. The use of simple and accessible materials demonstrated that effective teaching resources can be developed even in contexts with structural limitations, provided there is adequate pedagogical planning. The experience reinforces the relevance of active methodologies in Youth and Adult Education.
Keywords: Youth and Adult Education; Physics Teaching; Didactic Sequence; Scientific Literacy